Sistema prisional: gênero e encarceramento feminino no município de Guarapuava (PR) - Bugai, Fernanda de Araújo (2018)
Feminine jail population increase is disproportionate to the number of vacancies and prison units, which are designated to women in detention. As a result, women have been placed into units on a daily basis that are created by men and aimed at them, where guaranties and fundamental rights are relativized, since woman are inside men principle based structures. This thesis aimed to investigate, clarify and reference gender implications within the feminine prison system from the theme of women imprisonment, lack of prison units designated to women and the way they have been treated. For this purpose, firstly, one considers the prison system history in Brazil and the analysis of juridical prerogatives on national legal order, which are discussed by Alessandro Baratta (1999; 2002) in his Criminology, and by Penal Law and Penal Execution of Raúl Zaffaroni (1991; 2005; 2011) and Rogério Greco (2016) that pass by legislation created until the Federal Constituition advent in 1998, mainly in the criminal law enforcement 7.210/1984. In regards to the (non)existing suitable prison units for women are carrying out a sentence, one cites works of the sociologist Maria Tereza Citeli (2001) and jurist Olga Espinoza (2004) further supported by data extracted from INFOPEN – National Prison Data Collection, from National Prison Department – on female criminality and its expansion in recent years, and disproportionality to the number of vacancies that have been offered. In this study, gender theories are anchored to Judith Butler teachings (1987; 1998; 2010), and other authors on the same aspect, while one chose philosopher Michel Foucault (1967; 1999; 2004; 2012; 2014; 2016) to discuss about building subjectivities and because of his study about prisons regarding the way subjectivities are built when considering power relations. The analysis is based on interviews that were carried out focusing on building subjectivities of four women prisoners, in Guarapuava city, state of Paraná, whose sentence consists in closed system. Corpus was collected through women oral reporting, divided into two parts: before and after prison, characterizing every rupture in the interviewee’s lives, aiming at providing voice to them and to investigate their perception, while living under an ineffective system that reproduces stigmas, stimulate obliteration of women image and enhance sexist concepts in predominantly male places, where woman are featuring new lives with other perspectives, in a disciplinary dynamic that makes arise new people from micro-physics of power relations.